A changing sense of place: Geography and COVID‐19. (13th April 2021) - Bissell, David
Abstract: In this essay, I explain how geography offers important ideas to better understand what is happening to our sense of place during the COVID‐19 crisis, complementing the scientific understandings provided by epidemiologists and public health experts. I explain how geographical ideas relating to place and mobility can help us make sense of our current situation and consider what we might be feeling. These geographical ideas also provide us with important political tools to identify the new forms of inequality and hardship that are unfolding, prompting questions about how we should collectively respond to shape the future of place. Abstract : In this time of extreme uncertainty, we need geographical scholarship more than ever before. Geographical understandings of the COVID‐19 crisis are urgently required to make sense of the complexity of changing socio‐spatial relations. We can understand the changing meaning and significance of place during the COVID‐19 crisis through a range of perspectives.